KESULITAN BERPIKIR REFLEKTIF MATEMATIS SISWA DALAM MENYELESAIKAN SOAL PROGRAM LINEAR DI SMA NEGERI 5 KOTA TERNATE - Suryani Dahlan; Nurma Angkotasan; Hery Suharna (EDUKASI, 2022)
This study aims to describe the difficulties of students' mathematical reflective thinking in solving linear programming problems. This type of research is descriptive qualitative. Data collection techniques used are test instruments, interviews and documentation. Data analysis techniques in this study are data reduction, data exposure, data triangulation and conclusion drawing. The subjects of this study were students of class XI IPA 1 SMA Negeri 5 Ternate City, totaling 24 students, then representatives were selected based on the categories of mathematical ability, high, medium and low. The results showed that students with high mathematical ability had difficulty in reflective thinking, namely, 1) difficulties in connecting new knowledge with previous understanding, students needed accuracy in translating story questions into mathematical models, 2) difficulties in evaluating aspects of the completion process, students had difficulty remembering. return to function graph material to solve problems using the graph method. Students with moderate mathematical ability, 1) difficulty in connecting new knowledge with previous understanding, students need to be thorough in solving contextual problems, 2) difficulty in finding relationships and formulating solutions, students find it difficult to recall function graph material, difficult to shade the solution area, 3 ) difficulties in evaluating the aspect of the completion process, students find it difficult to prove the truth of the answers using the graphical method. Students with low mathematical ability, 1) difficulty in connecting new knowledge with previous understanding, students find it difficult to translate story questions into mathematical models, difficult to recall material on a two-variable linear inequality system, 2) difficulty in finding relationships and formulating solutions, students have difficulty find coordinate points, draw graphs, find intersection points, substitute corner points into objective functions. 3) difficulty in evaluating aspects of the completion process, students find it difficult to prove the truth of the answers obtained by the graphical method. The difficulties experienced by students in reflective thinking were caused by students not remembering the previous material related to linear programming, as well as students' difficulties in the dimensions of fact, concept and procedural knowledge.